Investigating assessment methods for the evaluation of actions mitigating nitrate loss to water - Cherry, Katherine (2011)
Diffuse nitrate (N) loss from agriculture is degrading surface and groundwater quality throughout Europe, leaving waterbodies at risk of not reaching targets set by the Water Framework Directive (WFD). Although a wide range of mitigation methods to reduce diffuse N loss have been identified, their appropriateness and effectiveness is not fully understood, especially at the catchment scale where a wide range of environmental and agricultural conditions exist. Suitable assessment methods are required to quantify the impact of mitigation and provide confirmation of their effectiveness. This study aimed to investigate the applicability of measurement and nutrient budgets for the evaluation of mitigation effectiveness at the field, farm and catchment scale; nutrient budgets represent an alternative approach where long transit times delay observable responses to mitigation in measurement. Investigations focused on two catchments in SW England, Milborne St Andrew (MSA) and Empool / Eagle Lodge (EMEL). Soil surface budgets were calculated for a total of 84 fields and farmgate surpluses / efficiency for 34 farms between 2005 and 2008. Soil mineral nitrogen (SMN) and porous pot (PP) sampling was undertaken in 115 and 57 fields respectively, and groundwater / stream water monitored at 171 sites. Sampling was carried out in 2007 and 2008, and a range of mitigation methods adopted on farm in 2008. Comparing results before and after mitigation, measurement approaches displayed contradictory responses – SMN significantly decreased, PP leached load and concentration significantly increased, and groundwater responses varied between sites. Results suggest an overriding sensitivity to environmental condition and the need for longer timescales especially at the catchment scale. Nutrient budgets at the field and farm scale tended to return lower surpluses post mitigation with 79% / 77% farms improving their farmgate surplus / efficiency. However only in EMEL were improvements in field or farm scale surpluses significant, a result of modest mitigation induced change and sensitivity to economic and environmental drivers. Comparing measurement and budget approaches, budgets were more responsive to changes in nutrient management in the short term and offered higher levels of farmer accountability. However long term measurements are required to provide confirmation that improvements in nutrient budgets transpire in water quality. As such a combined approach is suggested. With direct links to economic benefits likely to aid farmer engagement, and providing more complete representations of mitigation response and feedback, the use of farm scale budgets / efficiency over field scale budgets is advocated.